Degradation and hydrate phase equilibria measurement methods of monoethylene glycol - Alef, K.; Iglauer, Stefan; Barifcani, Ahmed (2019)
Monoethylene glycol (MEG), a common chemical used for the inhibition of gas hydrate formation may undergo degradation in the regeneration/reclamation process. Limited research exists on the effect of degradation of MEG on hydrate formation, production facilities and equipment especially in the presence of other chemical additives. The proposed method allows for streamlining the process of preparing, degrading and analysis of MEG solutions for hydrate testing and degradation products. • Procedure to prepare accurate MEG solutions avoiding oxidative degradation of MEG (i.e., controlling oxygen ingress).• Two methods are suggested to mimic field-like degradation of MEG solutions (i.e., degradation by reclamation and autoclave).• Adoption of the isochoric hydrate testing method while using a high pressure cell with the aid of a computer script to accurately evaluate hydrate phase equilibria conditions.